'Full-grown lambs': Immaturity and 'To Autumn' - Marggraf Turley, Richard (Romanticism on the Net, 2002)
AbstractWhile Keats's early publications were frequently derided by contemporary reviewers as puerile, the ode 'To Autumn' elicited generally approving comments. Indeed, the poem raised hopes in conservative quarters that Keats had, at last, 'grown up'. According to more recent critical orthodoxy, 'To Autumn' is regarded as having achieved a supreme, unimpeachable maturity. The overwhelming majority of scholarly addresses to the poem praise its poise and steadiness as it moves, resignedly, towards finality and closure. Countering such readings, I argue that 'To Autumn' actually represents one of Keats's most sustained and piercing attacks on the logic of mature power.